Nouthetic Counseling for Prison Inmates - Sang-Hee Kim (Theological Journal Kerugma, 2022)
Counseling is a field that is rapidly developing as the importance of the individual is recognized by society in the modern era. Counseling is also developing in Christian society, and the spectrum of theories and techniques is very wide depending on the perception of human beings and the perspectives of each party. Among them, there has already been a lot of approbation and criticism for Jay Adams, who opened a new horizon of biblical counseling through nouthetic counseling. However, no one can deny the contribution and influence of his counseling studies. In particular, a bigger effect can be expected for groups in special circumstances. One of those special groups is the prison inmates. They have their own peculiarities such as the isolated environment, psychological and physical stress, and heavy guilt, unlike the other groups of counselees. Indonesia is a country with a large population, but there is still insufficient interest in prison inmates. In addition to this, it is unfortunate that, like in most other countries, there are not many scholars who have studied this field until now. Now in Indonesia, outside volunteers are in charge of many parts of the ministry for inmates counseling and edification of inmates. However, the reality is that these volunteers lack professional counseling education and training. And most Christian volunteers use prayer and the Bible as their primary counseling tools.